Associations Between Short Video Exposure, Empathy and Attitudes Toward End‐Of‐Life Care Among Nursing Students: A Cross‐Sectional Study - Feifei Wang; Yitao Hu; Jingrui Wang; Yi Wang (Nursing Open, 2026)
ABSTRACT Aim This cross‐sectional study examined the associations between short video exposure, nursing students' empathy, and attitudes toward end‐of‐life (EOL) care, and tested whether perceived impact is statistically consistent with an indirect pathway in these relationships. Design A descriptive cross‐sectional study. Methods In total, 534 undergraduate nursing students were included. Data were collected using a self‐designed questionnaire, including the Attitudes Toward Care of the Dying Scale and the Jefferson Scale of Empathy–Health Professions Student version for empathy assessment. Statistical analysis for correlation and mediation analysis (PROCESS macro) was performed. Results 85.96% of students watch short videos for more than 30 min daily, with more than 60% of them viewing EOL‐related content. Students with prior caregiving experience or formal palliative care education showed significantly higher empathy and more positive attitudes ( p < 0.05). Exposure to medical and EOL‐related short videos was positively correlated with perceived impact, empathy, and positive EOL attitudes, with effect sizes ranging from very weak to modest ( r = 0.10 to 0.27). The data were consistent with an indirect pathway between short video exposure and empathy via perceived impact (indirect effect = 0.04; 95% bootstrap CI [0.01, 0.08]). However, for EOL attitudes, short video exposure showed a direct association rather than an indirect pathway via perceived impact (direct effect = 0.09, p < 0.01). Conclusion In this cross‐sectional study, short video exposure was modestly associated with nursing students' empathy, with data consistent with an indirect pathway via perceived impact; the observed associations explained only approximately 1% to 7% of the variance in the outcome variables. However, reshaping EOL attitudes may require more systematic education beyond brief video exposure. These findings are hypothesis‐generating and await validation through longitudinal and experimental research using standardized video content. Implications for Nursing Practice Nursing educators should consider integrating curated short video content into palliative care curricula to enhance students' empathy and perceived impact of end‐of‐life education. However, brief video exposure alone may be insufficient to reshape deeper end‐of‐life attitudes, suggesting the need for comprehensive, multi‐modal educational strategies.